PENGARUH PENGGUNAAN SISTEM INFORMASI AKUNTANSI DAN PEMAHAMAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus Pada Usaha Mikro Kecil Menengah Kota Yogyakarta) - Maknun, Luk Luk In (KRISNA: Kumpulan Riset Akuntansi, 2020)
This research aims to determine the effect of the use of accounting information systems and the understanding of SAK EMKM on the quality of the financial statements of MSME Yogyakarta. The population of this research is Micro, Small and Medium Enterprises (MSMEs) in the Yogyakarta City area. The sample in this study was selected through the random sampling method. The data collection method uses a questionnaire. Testing of research data is done by validity test, reliability test, while hypothesis testing with multiple linear regression analysis with the help of SPSS software version 18.0 The results of this study indicate that (1) the use of accounting information systems has a positive and significant effect on the quality of financial statements, (2) the understanding of SAK EMKM has a positive and significant effect on the quality of financial statements.compliance.